ANALISIS TUGAS POKOK FORUM TANGGUNG JAWAB SOSIAL LINGKUNGAN PERUSAHAAN (TJSL) DI KABUPATEN SIAK : SEBUAH TINJAUAN LITERATUR - Lilis Suriani; Herman; Muhammad Noor Ifansyah; Afrizal (Jurnal PubBis, 2023)
One of the objectives of the implementation of corporate social responsibility is to empower people who are in the poverty line in order to avoid adversity by implementing various community empowerment programs carried out by companies with various activities in the economic, social and environmental fields. However, in reality, many programs carried out by companies are not in accordance with the needs of the community which results in losses for the community. Siak regency has issued Regional Regulation Number 1 of 2013 concerning Corporate Social and Environmental Responsibility or abbreviated as TJSL. The main tasks are as follows: a) conduct an inventory of companies that are obliged to implement TJSL programs; b) facilitate TJSL programs; c) convey openly to the community TJSL programs; d) conduct field supervision of TJSL programs; e) evaluate the implementation of TJSL programs; and f) report the results of TJSL activities to the Regent. In this paper the author wants to see how the performance of the TJSL forum in order to carry out its main tasks in Siak District. This research uses a qualitative research method with a literature study approach by reviewing 15 research articles. Analysis techniques used by reviewing research results in the form of journals and books that are directly related to the research theme. The results of this study concluded that the performance of the Siak Regency TJSL Forum in carrying out its main duties has not been effective in accordance with the application of the theory used. It is hoped that in the future the TJSL Forum of Siak Regency can work as much as possible in carrying out its main duties so that what is done by the company for the people of Siak Regency is as expected, namely helping the government's duty to prosper.